Ethnic Relations and Nation-Building in Southeast Asia - Suryadinata, Leo (Book collections on Project MUSE., 2004)
Ethnic/racial relations have been a perennial theme in Southeast Asian studies. Current events have highlighted the tensions among ethnic groups and the need to maintain ethnic/racial harmony for national unity. This book analyses ethnic/race relations in Singapore, Malaysia, and Indonesia, with special reference to the roles of ethnic Chinese in nation-building. It brings together a group of established Southeast Asian scholars to critically examine some of the important issues such as ethnic politics, nation-building, state policies, and conflict resolution. These scholars of different ethnic origins present their own ethnic perspectives and hence make the book unique. This is the mostup-to-date book on ethnic/racial relations with special reference to the ethnic Chinese in three Southeast Asian countries.